Experimental investigation of steel-concrete composite beam to reinforced-concrete column joints with single plate shear connection. (15th October 2021) - Zhang, Jing; Hu, Xiamin; Gong, Shuhong; Wu, Junyi; Zhu, Wenwen; Ren, Cuiling
Highlights: Experiments were performed on SCCB to RC column exterior joints with SPS connection. Effect of the parameters on the behavior of joints were compared and discussed. A model for yield and ultimate moment of the joint was proposed and validated. Abstract: This paper focused on the behavior of steel–concrete composite beam (SCCB) to reinforced-concrete (RC) column exterior joint with single plate shear (SPS) connection under monotonic loading. Four SCCB to RC column exterior joints were constructed, and the test parameters were the longitudinal reinforcement ratio and high-strength bolt diameter. The failure modes, moment-rotation responses, strain distribution along composite beam depth, strain distribution of anchor bar and the influence of parameters were investigated. Compared with open literature, the influence of RC slab was also discussed. Finally, a calculation model accounting for the influence of RC slab was proposed to evaluate the yield moment and ultimate moment capacity of the joint under hogging moment. The test results showed that the longitudinal reinforcement ratio ( ρ sl ), high-strength bolt diameter ( d b ) and the RC slab effect had a great influence on static behavior of the SCCB to RC column joints with SPS connection. When ρ sl was increased from 0.57% to 0.98%, the ultimate moment was increased by 40.3%. When d b was increased from 16 mm to 20 mm, the ultimate moment was increased by 10.9%. Compared with the joints without RC slab, the ultimate moment of joints with RC slab was increased by 118% to 254%. Moreover, the proposed model provided a good prediction and laid a foundation for the design of SCCB to RC column joints with SPS connection.